ANALISIS PERILAKU KONSUMEN PROLL TAPE DI JEMBER - Risaldi, Feri; Widjayanti, Lenny; Kusmiati, Ati (Jurnal Sosial Ekonomi Pertanian, 2009)
Proll tape is a agroindustrial product which used agriculture product as a basic material. It is a diversification product from tape and mixed with some flavour. It can be found in the gift store. Proll tape marketing strategic will influence consumer behaviour in the decision buying. Consumer buy proll tape as a gift as beside on their own consumption. Consumer considers proll tape has a good quality so that it can fill consumer needed. Purpose of the research to find out the influence factors of proll tape consumer behavior, proll tape consumer behavior, and the relationship of income level toward to proll tape purchasing level. The research location use purposive methode with the type is descriptive and correlation methode. The sample extraction use convinience sampling. The analysis tools use factor analysis and chi square. Result of research indicate that : (1) The influence factors of proll tape consumer behavior are quality perception, motivation, promotion, location, supporting facility and packing. (2) the visible consumer behavior consist of purchasing frequency of proll tape between 2 until 3 purchased. Consumer buy proll tape monthly indefinitive. (3) there is not definitely relationship between income level toward to proll tape purchasing level. Key word : Proll tape, consumer behavior, income